PENDUGAAN MASA SIMPAN UDANG KEMAS BERBUMBU PADA SUHU DINGIN DENGAN METODE ARRHENIUS SHELF LIFE OF SPICED PACKED SHRIMP AT COLD TEMPERATURES WITH ARRHENIUS METHOD - Bagus Wahyu Kuncoro; Maria Erna Kustyawati; Dyah Koesoemawardani; Sri Hidayati (Jurusan Teknologi Hasil Pertanian, 2023)
Vannamei shrimp (Litopenaeus vannamei) are easily damaged after harvesting. Processing shrimp in a variety of ways, including dried and frozen whole, processed heads, and peeled. Immersty of things into seasoning liquid, which can result in seasoned instant shrimp products. The purpose of this study was to determine the shelf life of seasoned packaged shrimp stored at 10ºC, 20ºC, and room temperature (±30ºC) for 25 days and to observe changes in the water content of spiced shrimp. This study employed the Accelerated Shelf Life Testing (ASLT) method based on Arhenius with Microsoft Excel software, presented in graphs and tables. The findings were that seasoned shrimp had a shelf life of 25 days at 10 ºC, 20 days at 20 ºC, and 15 days at room temperature (30 ºC).